Determinants of Working Capital Management in Small and Medium Enterprises in Bauchi Metropolis - Ahmed, Ado; Umar, Iklimatu Adamu; Ishaya, Timothy Gwami; Musa, Dahiru (Kashere Journal of Management Sciences, 2024)
The main purpose of this study is to determine the working capital management in small and medium enterprises in Bauchi Metropolis. Specifically examining how profitability, sales growth, firm size and leverage affect working capital management. The total population of this study comprised the entire Small and medium enterprises registered with Bauchi Investment Corporation within the period of the study (2013-2017) from which a sample of fifty five was drawn using simple random sampling. Data was collected from annual reports and accounts of the sampled SMEs by the researchers. The study used OLS regression models to analyse the data collected. The main results reflect a negative and significant effect of profitability (ROA) on working capital where a positive and significant relationship between other explanatory variables (size, leverage and sales growth) with working capital was recorded.